Diclosure Of Thirs-Party Funding Arrangements aand The Existence of Third-Party Funders in International Investment Arbitration - Kadarisman, Abimanyu (UI Scholars Hub, 2019)
Third-party funding has been commonly used in International Investment Arbitration. Third-party funders increasingly usually finance the claimant who either (i) does not have sufficient funding to start legal proceedings, or (ii) adequately capitalized, but seek funding in order to minimize cash flow disruption and share risk during their arbitration proceedings. However, the notion of third-party funding gives rise to several issues; first, should funded parties be required to disclose their funding arrangements? Following the first research question, when does the funded party need to disclose the existence of a third-party funder? Then what legal measures can be taken to tackle the concern of transparency and disclosure in cases involving third-party funding? This research concentrates on the transparency and disclosure requirements, which is the central issue that influences further development and use of third-party funding arrangements in international arbitration. Analysis of relevant treaties, laws, guidelines, and case laws drives us to the conclusion that there exist measures and several drains the current international arbitration system that will serve a transparency system to control third-party funding. Hence, it would be appropriate for arbitration institute or investment treaties to take these tools into account in order to provide legal certainty for the disputing parties, arbitral tribunal, and ultimately, for the legal framework of third-party funding in investment arbitration..